2021
DOI: 10.1177/10600280211016856
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Opioid Administration in the Intensive Care Unit and Subsequent Use in Opioid-Naïve Patients

Abstract: Background Opioids are a mainstay of therapy for patients in the intensive care unit (ICU) as part of the analgesia-first approach to sedation. Despite knowledge of acute consequences of opioid based analgosedation, less is known about the potential long-term consequences, including the effect of opioid administration in the ICU on subsequent opioid use in opioid-naïve patients. Objective To evaluate the relationship between ICU opioid administration to opioid-naïve patients and subsequent opioid use following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…In total, 12 studies examined the use of analgesics in the posthospital discharge period (online supplemental file S3, table 4). 5 17 20 47–55 Analgesics examined included simple analgesics such as paracetamol alongside weak and strong opioids. Five studies examined the use of analgesia at hospital discharge,47 48 50 52 55 three studies were based in the ICU follow-up setting5 17 20 and six studies examined analgesics longitudinally across the critical care recovery period (up to 24 months following discharge 48 49 51 53–55.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 12 studies examined the use of analgesics in the posthospital discharge period (online supplemental file S3, table 4). 5 17 20 47–55 Analgesics examined included simple analgesics such as paracetamol alongside weak and strong opioids. Five studies examined the use of analgesia at hospital discharge,47 48 50 52 55 three studies were based in the ICU follow-up setting5 17 20 and six studies examined analgesics longitudinally across the critical care recovery period (up to 24 months following discharge 48 49 51 53–55.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies evaluating persistent opioid use after critical illness reported ICU opioid doses (23)(24)(25); among opioid-naïve patients, Krancevich et al (23) and Witcraft et al (24) found no association between ICU opioid dose and persistent opioid use), and Tollinche et al (25) observed that patients who received opioids in the ICU were less likely to receive an opioid prescription at discharge. Witcraft et al (24) found that intubation and hospital (but not ICU) opioid dose were associated with continuing opioids at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Yaffe ( 10 ), Wang et al ( 13 ), and Witcraft et al ( 24 ) reported that ICU LOS was not associated with persistent opioid use; in contrast, Wunsch et al ( 17 ) reported that ICU stays longer than 7 days were associated with greater risk of persistent opioid use. Krancevich et al ( 23 ) and Tollinche et al ( 25 ) reported that LOS after transfer to a non-ICU bed was associated with persistent opioid use, as was total hospital LOS for Witcraft et al ( 24 ). Due to collinearity, LOS data were not included in our multivariable model, but opioid-free days were associated with a reduced risk of persistent opioid fills, suggesting more aggressive opioid weaning, rather than limiting daily dose, may be a promising method to reduce persistent opioid use, but this has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid prescribing during inpatient and perioperative care is associated with long‐term opioid‐related harms 1–4 . Although focus on prescribing of opioid and benzodiazepines has recently increased, little is known regarding prescribing patterns following admission for COVID‐19 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Opioid prescribing during inpatient and perioperative care is associated with long‐term opioid‐related harms. 1 , 2 , 3 , 4 Although focus on prescribing of opioid and benzodiazepines has recently increased, little is known regarding prescribing patterns following admission for COVID‐19. 3 , 5 COVID‐19 has resulted in the hospitalization of millions of Americans, many of whom are without prior health conditions, and are opioid‐ and benzodiazepine‐naïve.…”
Section: Introductionmentioning
confidence: 99%